(untitled) (Journal of Global Accounting, 2022)
The study examines the impact of entrepreneurship education on poverty reduction among rural dwellers in Baruten local government area of Kwara state, Nigeria. Kwara state is ranked ninth with 20.4%poverty headcount rate in Nigeria (NBS, 2019). Entrepreneurship education was captured using mentorship and financial literacy. The specific objective of this study is to examine the impact of Mentorship and Financial literacy on poverty reduction among rural dwellers in the study area. The study used a survey design method. Structured and validated questionnaire was the instrument used in the collection of data. The respondents for this study were reached through their local associations and clubs. Out of the three hundred and eighty (380) copies of the questionnaire distributed, two hundred and ninety six (296) copies were properly filled and returned. Analysis of the data was done with regression analysis with the aid of SPSS version 25. The finding revealed that mentorship and financial literacy as predictors impacted negatively and have no positive effect on poverty reduction among rural dwellers as evident in their coefficient and probability value of (β1= - 0.135, p>0.05 and β2= - 0.411, p>0.05). This made the null hypothesis to be accepted. It is recommended that concerned agencies at the local government level should embark on campaigns to keep the rural dwellers abreast of mentorship and financial literacy programmes organized to assist entrepreneurs at the grassroots level.